Pengaruh Pengunaan Model Pembelajaran Value Clarification Technique (VCT) Terhadap Hasil Belajar Pkn Murid Kelas V SD Negeri Pa’bundukang Kecamatan Pattallassang Kabupaten Gowa - Nurul Pratiwi; Andi Sugiati; Roslyn Roslyn (Departement of Mathematics Education, 2024)
This research aims to determine the influence of the Value Clarification Technique (VCT) Model at SDN Pa'bundukang, Pattallassang District, Gowa Regency. The design used in this research is a preexperimental design with a one-group pretest-posttest design type. This research took a sample of 30 students. The research instrument is a pretest learning results test and then a posttest learning results test. Test validity is calculated by construct validity. To measure construct validity, you can use expert judgment. After testing the hypothesis, the tcount was 13.37 at a significant level of a= 0.05 and df = N – 2= 30-2= 28, so we obtained ttable = 2.048. Thus, H1 is accepted and Ho is rejected because 13.37 > 2.048, so it can be concluded that there is an influence of the Value Clarification Technique (VCT) Model on the Civics Learning Outcomes of Class V Students at SDN Pa'bundukang, Pattallassang District, Gowa Regency through the application of the Value Clarification Technique Model ( VCT) in Civics learning has increased.